Improving the stability of hybrid perovskite FAPbI3 by forming 3D/2D interfaces with organic spacers. Issue 60 (7th July 2022) - Kim, Yun-Sim; Ri, Chol-Hyok; Kye, Yun-Hyok; Jong, Un-Gi; Yu, Chol-Jun
Abstract : Organic spacer cations with aromatic rings are more favourable for enhancing the moisture stability of FAPbI3 3D/2D interfaces than those with aliphatic chains. The anilinium-based system shows the highest resistance to water penetration. Abstract : Interfaces composed of three-dimensional (3D) and 2D organic–inorganic hybrid formamidinium lead iodide (FAPbI3 ) linked by organic spacers (OSs) are studied using first-principles calculations. The OS cations with aromatic rings, like phenylethylammonium and anilinium (AN), are found to be more favourable for enhancing the stability of the 3D/2D interface than butylammonium with aliphatic chains. The AN-based interface shows the highest resistance to penetration of water molecules.